Intermuscular adipose tissue and muscle function in patients on maintenance hemodialysis - R. Gulsah Dilaver; Mert Demirci; Rachelle Crescenzi; Michael Pridmore; Lale A. Ertuglu; Andrew Guide; Robert Greevy; Baback Roshanravan; T. Alp Ikizler; Jorge L. Gamboa (Physiological Reports)
Abstract Sarcopenia is common in advanced chronic kidney disease (CKD), contributing to poor outcomes. Intermuscular adipose tissue (IMAT) may worsen muscle function through metabolic and inflammatory pathways. We conducted a cross‐sectional study comparing maintenance hemodialysis (MHD) patients and controls to assess IMAT and its associations. IMAT was measured via calf muscle MRI, and body composition (BMI, fat mass index), metabolic markers (hs‐CRP, TNF‐α, IL‐6, insulin resistance), and circulating cell‐free mitochondrial DNA (ccf‐mtDNA) were assessed. Muscle function was evaluated with handgrip strength. IMAT differences between groups were tested using inverse propensity weighting. We analyzed 25 MHD patients and 23 controls. Median age was 53 years, BMI 30.4 kg/m2, 83% were male, and 56% were African American. Baseline characteristics were similar between groups, except for race. MHD patients had higher IMAT (p < 0.01) and elevated TNF‐α, IL‐6, and hs‐CRP (p < 0.01). IMAT was positively correlated with IL‐6 in MHD patients and with TNF‐α in controls. Handgrip strength was inversely correlated with IMAT in the full cohort (p < 0.01). Our findings highlight the role of IMAT in inflammation and functional decline in CKD, suggesting its potential as a therapeutic target.